2019
DOI: 10.1021/jacs.9b06910
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed (Z)-Selective Hydroboration of Terminal Alkynes with Naphthalene-1,8-diaminatoborane

Abstract: The metal-catalyzed (Z)-selective hydroboration of terminal alkynes is synthetically challenging due to the usually (E)-selective nature of the hydroboration and the formation of the thermodynamically unstable (Z)-isomer. Herein, we report that N-heterocyclic-carbene-ligated ruthenium complexes catalyze the (Z)-selective hydroboration of terminal alkynes with H–B­(dan) (dan = naphthalene-1,8-diaminato), which generates a diverse range of synthetically valuable (Z)-alkenylboranes. Mechanistic studies, particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…Remarkably, the unmasking step could be avoided by utilizing the SMCC reaction condition developed by Saito group. [ 89 ] Interestingly, stereoisomers 20 , 21 , and 22 were synthesized from the different alkynyl‐B(dan)s via sequential introduction of appropriate aryl rings in a selective order of the three‐step SMCC reactions. Conceivably, when the TAEs with desired geometry are needed, this protocol would provide a practical and reliable choice allowing chemists to synthesize TAEs‐based AIEgens at will.…”
Section: Synthetic Protocols Toward Stereodefined Taesmentioning
confidence: 99%
“…Remarkably, the unmasking step could be avoided by utilizing the SMCC reaction condition developed by Saito group. [ 89 ] Interestingly, stereoisomers 20 , 21 , and 22 were synthesized from the different alkynyl‐B(dan)s via sequential introduction of appropriate aryl rings in a selective order of the three‐step SMCC reactions. Conceivably, when the TAEs with desired geometry are needed, this protocol would provide a practical and reliable choice allowing chemists to synthesize TAEs‐based AIEgens at will.…”
Section: Synthetic Protocols Toward Stereodefined Taesmentioning
confidence: 99%
“…( Z )‐Alkenyl–B(dan)s were also accessible by trans ‐hydroboration of terminal alkynes with H−B(dan), which was efficiently catalyzed by an NHC‐ligated ruthenium complex (Scheme 45). [39] …”
Section: B(dan)‐installing Reactionsmentioning
confidence: 99%
“…Much more robust C( sp 2 )–B(dan) bonds of aryl– and alkenyl–B(dan)s, which are actually unreactive under the above alkynyl–B(dan)’s conditions, were recently demonstrated to undergo direct SMC by Yoshida–Tsuchimoto [44] (Scheme 53) and Mutoh–Saito [39,45] (Scheme 54) independently. The use of t ‐BuOK as a base under anhydrous conditions is the key to the smooth coupling, and the direct SMC allowed various 2‐pyridyl–B(dan)s to be efficiently transformable into the respective products.…”
Section: Direct Smc With R–b(dan)mentioning
confidence: 99%
“…Calculations showed that the formation of the Z-olefin was thermodynamically less favourable than the E-olefin, implying a mechanistic origin for this effect. Accessing Z-olefins from terminal acetylenes is rather challenging, often requiring precious-metal catalysts and bespoke ligands, [29][30][31] making the exquisite stereoselectivity of hydrostibination with 1H both unusual and potentially valuable as a synthetic tool. The behaviour of 1H was particularly intriguing given that the previously reported AIBN-mediated addition of Ph2SbH to alkynes showed the opposite selectivity in favour of the E isomer (Z:E = 1:24).…”
Section: Introductionmentioning
confidence: 99%